Optimal Energy Scheduling for a Microgrid Encompassing DRRs and Energy Hub Paradigm Subject to Alleviate Emission and Operational Costs - Shahinzadeh, Hossein; Moradi, Jalal; Gharehpetian, Gevork B.; Fathi, S. Hamid; Abedi, Mehrdad (2018 Smart Grid Conference (SGC), 2018)
The interdependency of energy management strategies to economic, environmental and social sustainability issues has motivated many researchers to conduct a lot of kinds of studies on energy management topic. One of the innovative strategies for energy management modeling is the energy hub concept. Many industrial and residential loads are consuming different types of energy carriers. Hence, in order to minimize the costs and emission as well as maximization of profit, a model consists of the combination of all energy carriers must be employed. In this study, a new day-ahead energy scheduling approach with consideration of electric and thermal reserve requirements for a microgrid with multicarrier infrastructure is proposed. In this model, the energy hub functions as an active element which provides required energy through boiler and CHP and can supply thermal reserve through heat energy storage unit. The mathematical model is a multi-objective non-linear programming (MONLP), which is modeled and simulated in MATLAB software, and it is optimized applying cuckoo optimization algorithm (COA). In order to evaluate the proposed approach, the suggested model is compared with the separate scheduling satisfaction of thermal and electrical loads. The results indicate that the integrated model has lower operational costs and diminishes the air pollution emissions. Besides, the elastic loads are profited more through the incorporation of energy hub model.